Worldwide phylogeography of rough‐toothed dolphins ( Steno bredanensis ) provides evidence for subspecies delimitation - G. Renee Albertson; Alana Alexander; Frederick I. Archer; Susana Caballero; Karen K. Martien; Lenaïg G. Hemery; Robin W. Baird; Marc Oremus; M. Michael Poole; Deborah A. Duffield; Robert L. Brownell; Dan Kerem; et al. (Marine Mammal Science, 2022)
Rough‐toothed dolphins ( Steno bredanensis ) have a global tropical and subtropical distribution with oceanic, neritic, and island‐associated populations. To inform conservation and management for this species, we used sequences from the mtDNA control region ( n = 360), mitogenomes ( n = 19), and six nuclear introns ( n = 35) to provide multiple lines of evidence to critically evaluate the potential taxonomic status of rough‐toothed dolphins. Using samples from the Pacific, Indian, and Atlantic Oceans, we examined the null hypothesis that rough‐toothed dolphins are one panmictic species and the alternate hypothesis of oceanic subspecies. Phylogenetic analyses of mitogenomes revealed a private Atlantic clade sister to a larger cosmopolitan clade including individuals from all tropical and subtropical oceans. We dated the split between the Atlantic clade and the cosmopolitan clade to 890,000 years ago. We determined that Atlantic rough‐toothed dolphins could be correctly diagnosed with 98% accuracy with the mtDNA control region and calculated the net nucleotide divergence as 0.02. Population level analyses revealed significant genetic differentiation using mtDNA among most regions, while significant differentiation using nuclear markers occurred only between the Atlantic and the Indian/Pacific regions. Therefore, the oceanic divergence and diagnosability of rough‐toothed dolphins in the Atlantic and the Indian/Pacific Oceans meet proposed criteria for recognition as two subspecies.

Genetic evidence for a family structure in stable social aggregations of the Australian lizard Egernia stokesii - M. G. Gardner; C. M. Bull; S. J. B. Cooper; G. A. Duffield (Molecular Ecology, 2001)
In this study we used data from six unlinked microsatellite loci to examine stable aggregations of Egernia stokesii , from a population in the southern Flinders Ranges of South Australia. We show that these aggregations are comprised of breeding partners, their offspring from two or more cohorts, and related adults, providing the first genetic evidence of a family structure in any lizard species. Despite this high level of relatedness within aggregations, most breeding pairs were unrelated and partners were less closely related to each other than they were to other potential within‐group partners. Where individuals dispersed, both sexes usually moved to social groups close to their natal group. Although both sexes showed natal philopatry, there was some evidence that females in groups were more related than males in groups. These data suggest that an active choice of unrelated partners and male‐biased dispersal may be the mechanisms used by E. stokesii to avoid inbreeding within groups.